Assessment and management of agitation in psychiatry: Expert consensus. (17th February 2016) - Garriga, Marina; Pacchiarotti, Isabella; Kasper, Siegfried; Zeller, Scott L.; Allen, Michael H.; Vázquez, Gustavo; Baldaçara, Leonardo; San, Luis; McAllister-Williams, R. Hamish; Fountoulakis, Konstantinos N.; Courtet, Philippe; Naber, Dieter; et al.
Abstract: Background Psychomotor agitation is associated with different psychiatric conditions and represents an important issue in psychiatry. Current recommendations on agitation in psychiatry are not univocal. Actually, an improper assessment and management may result in unnecessary coercive or sedative treatments. A thorough and balanced review plus an expert consensus can guide assessment and treatment decisions.Methods An expert task force iteratively developed consensus using the Delphi method. Initial survey items were based on systematic review of the literature. Subsequent surveys included new, re-worded or re-rated items.Results Out of 2175 papers assessing psychomotor agitation, 124 were included in the review. Each component was assigned a level of evidence. Integrating the evidence and the experience of the task force members, a consensus was reached on 22 statements on this topic.Conclusions Recommendations on the assessment of agitation emphasise the importance of identifying any possible medical cause. For its management, experts agreed in considering verbal de-escalation and environmental modification techniques as first choice, considering physical restraint as a last resort strategy. Regarding pharmacological treatment, the "ideal" medication should calm without over-sedate. Generally, oral or inhaled formulations should be preferred over i.m. routes in mildly agitated patients. Intravenous treatments should be avoided.